28S rDNA as an alternative marker for commercially important oyster identification. (August 2016) - Mazón-Suástegui, José Manuel; Fernández, Natalia Trabal; Valencia, Ignacio Leyva; Cruz-Hernández, Pedro; Latisnere-Barragán, Hever
Abstract: Seafood marketing requires certificated products generated under sustainable management practices. The oyster farming is profitable but its identification, and hence certification is difficult due to their phenotypic plasticity. This study intends to prove that 28S rRNA has a comparable level of resolution for the correctly oyster species identification. Additionally, the resolution level of mitochondrial cytochrome c oxidase subunit I (COI) and nuclear inter-transcribed spacer 1 (ITS-1) were assessed. Under a phylogenetic approach, levels of genetic divergence intra and inter specific and nucleotide substitution saturation, were analyzed from 196 sequences of 9 oyster species belonging to the subfamilies Crassostreinae ( Crassostrea gigas, Crassostrea sikamea, Crassostrea virginica, Crassostrea rhizophorae, Crassostrea corteziensis and Crassostrea columbiensis ), Striostreinae ( Saccostrea palmula and Striostrea prismatica ) and Ostreinae ( Ostrea chilensis ). The results showed the higher genetic divergence for ITS-1 followed by COI and 28S. However, the substitution saturation analysis shown that the phylogenetic signal of ITS-1 was unreliable. For COI, the phylogenetic signal was moderate and problems to separate ( S. palmula and S. prismatica ) and obtain ( C. corteziensis and C. columbiensis ) haplotypes, were experienced. Finally, although the 28S showed the lower level of genetic divergence, their saturation analysis showed a reliable phylogenetic signal and correctly identify all the oyster species and clustered them by subfamily and geographic origin. Hence, the 28S fragment analyzed shown that could be used as an alternative marker and presented advantage due to its methodological simplicity and confidence for species identification. Highlights: An alternative molecular marker for oyster identification is proposed. Description of methodological problems for commercial oyster species identification. Assessment of phylogenetic signal of three molecular markers (COI, ITS-1 and 28S). First report of sequences of COI, ITS-1 and 28S for C. corteziensis, C. columbiensis, S. palmula and S. prismatica oysters.